UNDERSTANDING THE COMPETENCIES AS GLOBAL CITIZEN - ANGGRAENI, ADE IRMA (JOURNAL OF RESEARCH IN MANAGEMENT, 2019)
The industrial revolution is a reality that must be faced by every country. This condition hasan impact on increasing interdependence between country located in an area in the form ofcooperation in various fields. Industrial revolution gives an essential challenge to improvethe quality of resources human power that can establish cross-cultural interactions to beable to address every opportunity of good cooperation. One component that needs to bepossessed by human resources in the era of the industrial revolution, especially the younggeneration of Indonesia is the cross-cultural communication competence with knowledge,understanding, self-confidence and cultural identity through the experience of interactingwith individuals from different cultural backgrounds. The young generation of Indonesianeeds to build a global mindset and play an active role in building harmonious cooperationin achieving the agenda of the industrial revolution. This phenomenon is essential so thatIndonesia's human resources are not just spectators, but can determine the success of theempowered nation competitiveness. This study aims to analyse affective, cognitive andconative elements in forming cross-cultural communication competencies. This researchalso examines the influence of the dimensions of cross-cultural communication and attitudestowards global citizenship towards the intention to work together across cultures. Theresearch sample was taken using a purposive sampling method. Data were collected usingsurvey methods with questionnaire techniques. Respondents in this study were students atthree universities in Central Java.